Bose-Einstein condensates in 2D with time-periodic scattering length - Abdullaev, F. K.; Caputo, J. G.; Kraenkel, Roberto André [UNESP]; Malomed, B. A. (Kluwer Academic/plenum Publ, 2004)
We discuss two-dimensional Bose-Einstein Condensates (BEC) under time-periodic variation of the scattering length. In particular we argue that for high-frequency variation there exist stable self-confined condensates without an external trap, when the do component of the scattering length is negative. Our results are based on a variational approximation, on direct averaging of the Gross-Pitaevskii equation and on numerical simulations.